The Effect of Game Based Learning Assisted by Fun Card Puzzle on the Conceptual Understanding of Class 5th Elementary School Students - Farin Hanifatun Nuha; Kartika Yuni Purwanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Concept understanding is that students understand the meaning of a concept. So the authors apply an understanding of the concept by using a game-based learning model assisted by fun card puzzles to find out students' understanding of concepts. This study uses a quantitative method and an experimental form, namely Quasi Experimental Design with Pre-test Post-test Design. The population of this study were fifth grade students at Lerep 02 and Lerep 05 Elementary School. The data analysis technique used was the sample t test and simple linear regression test. The results show that there is an influence of the game-based learning model assisted by fun card puzzles with proven tcount = 3.712 while ttable = 2.131, with significance level 0.002. It can be concluded that the game-based learning model assisted by fun card puzzles has an effect on students' conceptual understanding